Isoclinism of crossed modules. (May 2016) - Odabaş, A.; Uslu, E.Ö.; Ilgaz, E.
Abstract: In this paper, we introduce the notion of isoclinism among crossed modules and describe various properties of the notion. We give an algorithm for checking isoclinism among crossed modules and apply the algorithm (implemented in GAP) to classify certain crossed modules.